A MATHEMATICAL MODEL FOR THE TRANSMISSION DYNAMICS OF HIV/AIDS IN A TWO-SEX POPULATION CONSIDERING COUNSELING AND ANTIRETROVIRAL THERAPY (ART). (2012) - KIMBIR, RICHARD A.; UDOO, MARTIN J. I.; ABOIYAR, TERHEMEN
No abstract available